Word Square Strategy To Increase Interest In Learning Science In Class V SD Negeri 09 Ngringo - Aji, Dhian Ardhanari Bayu (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This type of research is Classroom Action Research (CAR).  Data collection techniques in this study used observation, interviews, tests, and documentation techniques. The instruments in data collection are observation sheets, interview sheets, syllabus, lesson plans, and tests. The data analysis technique used is an interactive analysis technique which consists of data reduction, data exposure, and drawing conclusions. The result of this classroom action research is that there is an increase in students' interest in learning science, seen from the indicators of achievement of interest in learning which include: participation, attention, and a sense of enjoyment in learning activities which have increased.The percentage of students' learning interest participating in learning activities in the pre-cycle was 39.53%, in the first cycle was 65.11%, and in the second cycle was 86.04%, while students who paid attention to learning activities in the pre-cycle were 34 .88%, in the first cycle of 58.13%, and in the second cycle of 83.71%. While students who are happy in learning activities in the pre-cycle are 30.32%, in the first cycle are 46.50%, and in the second cycle are 81.39%. This study concludes that the application of the Word Square strategy can increase the interest in learning science for fifth grade students at SD Negeri 09 Ngringo.